Thermal, mechanical, thermo-mechanical and morphological properties of graphene nanoplatelets reinforced green epoxy nanocomposites - Salit @ Sinon, Mohd Sapuan; Jameel, Yusuf; Hassan, Mohd Roshdi; Rashid, Umer; Ilyas, Ra (John Wiley & Sons, Inc., 2023)
The efficient inclusion of GNPs (graphene nanoplatelets) as an effective nano-fillers for green polymer matrices produced with 28% of carbon originating from biomass tends to significantly improve mechanical and thermal properties. In the present work, green epoxy nanocomposites with low loading of (0.1, 0.25, and 0.5) wt% of the GNPs were made using a solution blending technique using acetone as the solvent. In mechanical stirring, the ultrasonic bath was used to ensure the efficient dispersion of GNPs within green epoxy. The resulting nanocomposites were comprehensively characterized and compared to unfilled green epoxy. Different tools were used to appraise morphological, thermal, thermo-mechanical, and mechanical behavior. The results confirmed through FE-SEM showed an optimal dispersion of GNPs with nanocomposites. The thermal degradation temperature (Td) of GNPs curve with 0.25 wt% loading was shifted toward higher temperature (from 336°C to 342°C) due to low percentage of loading of GNPs which showed an enhance thermal stability of polymer matrix with 0.25 wt% loading. The mechanical results were also in lined with previously published literature, in the tensile test 6.45% and hardness 13.3% increment was achieved. Overall, the results underscored significant improvements in green nanocomposite performance with low wt% of GNPs.